2020
DOI: 10.1149/1945-7111/ab632c
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal—Carbon Bond Enthalpies as Descriptor for the Electrochemical Stability of Transition Metal Carbides in Electrocatalytic Applications

Abstract: Transition metal carbides are used for various applications such as hard coating, heterogeneous catalysis, catalyst support material or coatings in fuel cell applications. However, little is known about the stability of their electrochemically active surface in aqueous electrolytes. Herein, the transition metal—carbon bond enthalpy is proposed as stability criterion for various transition metal carbides. The basis is an oxidation mechanism where the rate determining step is the metal—carbon bond cleavage under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…Early transition metal carbides were reported to exhibit metallic conductivity, high corrosion resistance and are able to strongly bind to noble metals such as Pt anchoring it in place . Our own research revealed stabilization of tungsten carbide compared to bare tungsten, and we were able to identify the metal‐carbon bond enthalpy as stabilization criterion for various metal carbides . Titanium carbide (TiC) shows a maximum formation and bonding enthalpy compared to other transition metal carbides resulting in enhanced thermodynamic stabilization .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Early transition metal carbides were reported to exhibit metallic conductivity, high corrosion resistance and are able to strongly bind to noble metals such as Pt anchoring it in place . Our own research revealed stabilization of tungsten carbide compared to bare tungsten, and we were able to identify the metal‐carbon bond enthalpy as stabilization criterion for various metal carbides . Titanium carbide (TiC) shows a maximum formation and bonding enthalpy compared to other transition metal carbides resulting in enhanced thermodynamic stabilization .…”
Section: Resultsmentioning
confidence: 81%
“…Our own research revealed stabilization of tungsten carbide compared to bare tungsten, and we were able to identify the metal‐carbon bond enthalpy as stabilization criterion for various metal carbides . Titanium carbide (TiC) shows a maximum formation and bonding enthalpy compared to other transition metal carbides resulting in enhanced thermodynamic stabilization . We used exemplarily readily available TiC and deposited multiple Pt‐layers on a 510 nm thick magnetron sputtered TiC thin film via atomic layer deposition (ALD) offering high control over the final metal film .…”
Section: Resultsmentioning
confidence: 99%
“…The increased covalent bonding character is ascribed to the observed stability enhancement and a positive shift in the oxidation onset potential, i.e., a higher electrochemical nobility was observed. 44 For some metal carbides, metal dissolution takes place at similar potentials (∼0.85 V RHE for TiC) where usually only noble metal oxidation, such as that on Pt (∼0.95 V RHE ), takes place and demonstrates the potential of these materials. 5 Besides carbides, the stability of a variety of phosphides and oxides can be magnitudes higher compared to that of their bare metal congeners depending on the material and operation conditions.…”
Section: What Are the Dominant Degradation Pathways In Aqueous Electr...mentioning
confidence: 99%
“…While Pourbaix diagrams mostly focus on bare metals and the formed hydroxides or oxides, thermodynamic stabilization has been found, for instance, for metal carbides. 5,44 Not only does the thermodynamic stability increase but also the experimentally observed oxidation can differ drastically compared to that of the bare metal. The covalent character of the metal−carbon bond and the difference in electronegativity create a polar surface, leading to electron density transfer from the metal sites to the neighboring heteroatom sites.…”
Section: What Are the Dominant Degradation Pathways In Aqueous Electr...mentioning
confidence: 99%
“…Moreover, because metal is introduced on the carbon support, the oxidation potential of the catalysts and the binding energy with oxygen will change [219], resulting in an unstable ORR catalytic performance. The ultimate goal is for the catalyst to concurrently have an excellent catalytic activity and stability [220] and the introduction of multiple components (both activity-promoting components and stability-promoting components) may be a feasible idea for preparing functional carbon supports, however, more research and exploration is needed.…”
Section: Molybdenum Carbidementioning
confidence: 99%